The Role of Leadership in Organizational Implementation and Sustainment in Service Agencies - Moullin, Joanna; Ehrhart, M.; Aarons, G. (2018)
© 2017, The Author(s) 2017. Implementation is posited as a multiphasic process, influenced by a range of factors, within a multilevel context. While there appears to be a general consensus that every implementation initiative will have a unique combination of influences that vary in importance across the implementation phases, leadership is an essential tenant throughout implementation frameworks, models, and theories. The exploration, preparation, implementation, sustainment framework is used to explore leadership, at both the inner organizational level and the outer system level, and to guide a discussion regarding three critical issues involved in implementation (organizational climate/culture, collaborative relationships, and contracting). Finally, three implementation strategies focused on improving leadership are described in order to provide examples of these issues.